Major Changers : Using Sankey Diagrams For Student Retention & Graduation - Herbison, Kari; Kraft, Nicole; Cieslewicz, Lance (My University, 2018)
The University of Wisconsin-Eau Claire is always looking for ways to improve retention and graduation rates. The Office of Institutional Research completed a project focusing on student movement with the goal of following student major changes from term to term. Previous “Major Changers” projects attempted to analyze this data in a tabular format which was difficult to read and understand. A Sankey diagram was used to better visualize this data. The Sankey diagram is an innovative way to visualize the flow of data between points in time. These diagrams have not been very widespread in higher education due to the complexity of creating the graphic. Additionally, many universities do not have organized retention and graduation data to complete a Sankey diagram.
Color poster with text, images, and table.
Keywords: Posters; Sankey diagrams; Graduation; College students--Wisconsin--Eau Claire; Student retention